1974
DOI: 10.1111/j.1365-2621.1974.tb02942.x
|View full text |Cite
|
Sign up to set email alerts
|

The Aroma of Canned Beef: Application of Regression Models Relating Sensory and Chemical Data

Abstract: The purpose of this investigation was to determine general relations between instrumental and sensory aroma data from a reference material consisting of a large set of different types of beef samples analyzed during several years. The relations obtained in this way have been tested on independent “unknown” samples. Different models have been used, basically derived from Stevens' law and formulated in analogy with models used in other psychophysical contexts. From the reference material a great number of highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1974
1974
2002
2002

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…A somewhat similar technique has been used on soy sauce by Tanaka and Saito (1969). Models for correlation between instrumental and sensory data were applied according to Persson and von Sydow (1974b).…”
mentioning
confidence: 99%
“…A somewhat similar technique has been used on soy sauce by Tanaka and Saito (1969). Models for correlation between instrumental and sensory data were applied according to Persson and von Sydow (1974b).…”
mentioning
confidence: 99%
“…Sulfides and 3-methylbutanal were among certain com- pounds implicated in burnt aroma of canned beef by Persson and von Sydow (1974). Further studies at our laboratories have indicated a positive correlation between the odor descriptions roast meat and burnt.…”
Section: Resultsmentioning
confidence: 72%
“…All results must be interpreted with caution, and independent validation is essential. Simply because two variables are correlated does not imply that one necessarily causes the other (Piggott, 1990), although the repeated occurrence of similar compounds in predictive models would make it likely that causative stimuli were involved (Peerson & von Sydow, 1974).…”
Section: Assessment Offzavour Components and Fractionsmentioning
confidence: 99%